Real-world treatment outcomes and clinicopathologic and molecular determinants of response to first-line lenvatinib in patients with advanced follicular cell-derived thyroid cancer - Kara M. Ruicci; Yangqing Deng; Tian Xiao; Antoine Eskander; David Goldstein; Ozgur Mete; Aruz Mesci; Jelena Lukovic; Monika K. Krzyzanowska; Carly C. Barron; Lucy X. Ma (BJC Reports)
Abstract Background There is a paucity of real-world data regarding lenvatinib for locally-recurrent, metastatic and RAI-refractory thyroid cancer. Here we examined the efficacy of first-line lenvatinib in a genomically-characterized cohort and identified clinicopathological/molecular correlates of drug response. Methods Patients with advanced follicular cell-derived thyroid cancer who underwent NGS at Princess Margaret Cancer Centre and commenced first-line lenvatinib monotherapy between 2015-2023 were included. Kaplan-Meier method, log-rank tests and univariable/multivariable proportional hazard models were employed. Results In total, 77 patients were included (48% female, majority papillary (52%), poorly differentiated (17%) or invasive encapsulated follicular variant papillary (16%)). Most (79%) underwent total thyroidectomy and adjuvant RAI (median cumulative dose 231 mCi). At lenvatinib initiation, median age was 62.9 years, 68% were ECOG performance status ≥2, 81% had lung metastases, 53% had bone metastases and 8% had liver metastases. Most patients started with ≤14 mg of lenvatinib daily. Median time to treatment discontinuation was 33 months. Older age, ECOG ≥ 2, liver metastases and TP53 mutation(s) were associated with shorter time to treatment discontinuation; ECOG ≥ 2 and TP53 mutation(s) remained significant on multivariable analysis. Conclusion Our findings reinforce the clinical efficacy of lenvatinib in advanced thyroid cancer patients with heterogenous clinicopathologic/molecular features and highlight variables for future treatment stratification.